1997
DOI: 10.1101/gr.7.7.725
|View full text |Cite
|
Sign up to set email alerts
|

A Transcript Map for the 2.8-Mb Region Containing the Multiple Endocrine Neoplasia Type 1 Locus

Abstract: Multiple endocrine neoplasia type 1 (MEN 1) is an inherited cancer syndrome in which affected individuals develop multiple parathyroid, enteropancreatic, and pituitary tumors. The locus for MEN1 is tightly linked to the marker PYGM on chromosome 11q13, and linkage analysis places the MEN1 gene within a 2-Mb interval flanked by the markers D11S1883 and D11S449. Loss of heterozygosity studies in MEN 1 and sporadic tumors suggest that theMEN1 gene encodes a tumor suppressor and have helped to narrow the location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 42 publications
2
82
0
Order By: Relevance
“…Examination of the chromosome 11 sequence revealed perfect homology with a previously identified gene, Alpha (29,30), which is fused to the first intron of TFEB (Fig. 4A).…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Examination of the chromosome 11 sequence revealed perfect homology with a previously identified gene, Alpha (29,30), which is fused to the first intron of TFEB (Fig. 4A).…”
Section: Resultsmentioning
confidence: 70%
“…The Alpha gene is on chromosome 11 (29,30) and produces a 7.5-to 8.5-kb intronless transcript (GenBank accession number AP000769.4). The region of Alpha sequenced in the TFEB fusion corresponds to nucleotides 733-1580 (GenBank accession number AF203815).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Database searches revealed that this sequence has been described as part of different ESTs. Two separate ESTs were mapped to chromosome 11q13 in a radiation hybrid map (James et al, 1994) and later identified to belong to a single transcript of 8.5 kb (Guru et al, 1997), preliminarily named a gene (GenBank Acc AF203815). This transcript was isolated again in searches for translocation breakpoints at 11q13 (van Asseldonk et al, 2000).…”
Section: Malat-1 -A Noncoding Rnamentioning
confidence: 99%
“…[23][24][25][26] While a short and a long transcript previously identified as MENe (Neat1-1) and MENb (Neat1-2), respectively. 25,27 are generated from the same promoter, Neat1-1 alone cannot induce paraspeckle formation since specific depletion of Neat1-2 leads to disruption of paraspeckles. 25 While paraspeckles detected by RNA FISH of Neat1 appeared as round foci when visualized under a confocal microscope, we showed that they appeared more likely as oblong structures with smaller dimensions after use of a combination of Neat1 RNA FISH and Super Resolution STORM analysis (as designed in Fig.…”
mentioning
confidence: 99%